Comprehensive Characterization and Validation of Chromosome-Specific Highly Polymorphic SSR Markers From Pomegranate (Punica granatum L.) cv. Tunisia Genome - Patil, Prakash Goudappa; Singh, Nripendra Vikram; Bohra, Abhishek; Raghavendra, Keelara Puttaswamy; Mane, Rushikesh; Mundewadikar, Dhananjay M.; Babu, Karuppannan Dhinesh; Sharma, Jyotsana (Frontiers in Plant Science, 2021)
The SSR survey of ‘Tunisia’ genome (296.85 Mb) identified a total of 365279 perfect SSRs spanning eight chromosomes, with a mean marker density of 1230.6 SSRs/Mb. We found a positive trend in chromosome length and the SSR abundance; as marker density enhanced with a shorter chromosome length. The highest number of SSRs (60708) was mined from chromosome 1 (55.56 Mb), whereas the highest marker density (1294.62 SSRs/Mb) was recorded for the shortest chromosome 8 (27.99 Mb). Further, we categorized all SSR motifs into three major classes based on their tract lengths. Across the 8 chromosomes, the class III had maximum number of SSR motifs (301684, 82.59 %), followed by the class II (31056, 8.50 %) and the class I (5003, 1.37%). Examination of the distribution of SSR motif types within a chromosome suggested the abundance of hexanucleotide repeats in each chromosome followed by dinucleotides, and these results are consistent with ‘Tunisia’ genome features as a whole. Concerning major repeat types, AT/AG was the most frequent (14.16%), followed by AAAAAT/AAAAAG (7.89%), A/C (7.54%), AAT/AAG (5.23%), AAAT/AAAG (4.37%) and AAAAT/AAAAG (1.2 %) types. We designed and validated a total of 3839 class I SSRs in the ‘Tunisia’ genome through ePCR and found 1165 (30.34%) SSRs producing a single amplicon. Then, we selected 906 highly-variable SSRs (>40 nt) from the ePCR-verified class I SSRs and in silico validated across multiple draft genomes of pomegranate, which provided us a subset of 265 highly polymorphic SSRs. Of these, 235 primers were validated on six pomegranate genotypes through wet-lab experiment. We found 221 (94 %) polymorphic SSRs on six genotypes, and 187 of these SSRs had ≥ 0.5 PIC values. The utility of the developed SSRs was demonstrated by analyzing genetic diversity of 30 pomegranate genotypes using 16 HvSSRs spanning 8 pomegranate chromosomes. In summary, we developed a comprehensive set of highly polymorphic genome-wide SSRs. These chromosome-specific SSRs will serve as a powerful genomic tool to leverage future genetic studies, germplasm management and genomics-assisted breeding in pomegranate.